Expedient of the Practical Principle at the Time of Doubt whether an âObligatoryâ is NafsÄ« (for itself) or ghayrÄ« (for another) - Ã™Â…Ã˜Â³Ã˜Â¬Ã˜Â¯Ã˜Â³Ã˜Â±Ã˜Â§Ã˜Â¦Ã›ÂŒ, Ã˜ÂÃ™Â…Ã›ÂŒÃ˜Â¯; Ã˜Â§Ã˜Â¬Ã™ÂˆÃ˜Â¯Ã˜Â§Ã™Â†Ã›ÂŒ, Ã˜ÂÃ˜Â¨Ã›ÂŒÃ˜Â¨ (Ã™ÂÃ™Â‚Ã™Â‡ Ã™Âˆ Ã˜Â§Ã˜ÂµÃ™ÂˆÃ™Â„)
There has been disagreement among uá¹£Å«lÄ«s concerning the execution of the practical principle â at the time of doubt whether an obligatory is nafsÄ« (for itself) or ghayrÄ« (for another) â and various viewpoints are brought up, to the extent that ÄkhÅ«nd KhurasanÄ« has devised a double division and finally, the late NÄâÄ«nÄ« devised a triple division that has been approved by the majority of scholars. In this research, however, we have achieved a new triple division, which has been unprecedented in the opinions of the early scholars and is, in a way, a combination of the divisions presented by KhÅ«âÄ« and NÄâÄ«nÄ«.